(untitled) (Diálogos críticos en educación: voces y experiencias., 2024)
David Arellano Gaul Luis Montaño Hirose José Alfredo Zavaleta Betancourt Laura Zamudio González Rebeca Elizabeth Contreras López Rubén Darío Jiménez Rosado Irma Alicia García Contreras